Characterization of Metakaolin from Wassa Kaolin and Its Potential as Adsorbent for the Regeneration of Used Engine Lubrication Oil - Ralph Kwakye; Albert Aniagyei; Bright Yaw Vigbedor; Jonathan Osei-Owusu; Bonface Yeboah Antwi; Anthony Selorm Kwesi Amable; George Edusei; Bright Kwakye-Awuah (Advances in Materials Science and Engineering)
Metakaolin is an anhydrous clayey material obtained by the calcination of kaolin. This material has been utilized as a valuable substitute or additive for concrete/cement mixtures and many other applications. The current study is on the production and characterization of metakaolin together with its adsorbent properties for the purification and regeneration of spent lubrication oil. Metakaolin was produced from the calcination of kaolin from Wassa in the Western region of Ghana. The metakaolin was characterized by using X-ray fluorescence (XRF), X-ray diffractometry (XRD), scanning electron microscopy (SEM) coupled with energy dispersive X-ray (EDX), and Fourier transform infra-red (FT-IR). The metakaolin was then used as an adsorbent in the regeneration of the engine lubrication oil, mimicking the acid-clay percolation process. The test results show that the efficiency of metakaolin in removing heavy metals from the used oil using an atomic absorption spectrometer (AAS) was 13.25% for Fe, 25.37% for Cr, 94.36% for Zn, and 33.33% for Cu. The viscosity index of the regenerated oil was 118 compared to that of the virgin oil, which was 115. The regenerated oil had 79% saturates, 6% carbon residues, and 18% aromatics compared to the commercial virgin oil, which contained 84% saturates, 5% carbon residue, and 11% aromatics. This indicated that metakaolin is a better adsorbent for regenerating the used lubrication oil.